2016
DOI: 10.1136/bmjspcare-2016-001179
|View full text |Cite
|
Sign up to set email alerts
|

Narrative medicine and death in the ICU: word clouds as a visual legacy

Abstract: ObjectiveThe Word Cloud is a frequent wish in the 3 Wishes Project developed to nurture peace and ease the grieving process for dying critically ill patients. The objective was to examine whether Word Clouds can act as a heuristic approach to encourage a narrative orientation to medicine. Narrative medicine is an approach which can strengthen relationships, compassion and resilience.DesignWord Clouds were created for 42 dying patients, and we interviewed 37 family members and 73 clinicians about their impact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…A strictly protocolized program would likely inhibit individuals from identifying creative ways of relating to each other, potentially reducing the value of human connections realized through the program. Current and previous research about 3WP has found the meaning of these human connections to be one of the most important strengths of the program [6,7,[9][10][11]21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strictly protocolized program would likely inhibit individuals from identifying creative ways of relating to each other, potentially reducing the value of human connections realized through the program. Current and previous research about 3WP has found the meaning of these human connections to be one of the most important strengths of the program [6,7,[9][10][11]21].…”
Section: Discussionmentioning
confidence: 99%
“…While not planned a priori, this analysis describes how the 3WP was initiated and eventually integrated organically into practice without a rigid protocol in 9 ICUs with their own culture in Canada and the United States. Family perspectives, though previously obtained about different aspects of this program [6,7,[9][10][11], were not sought about program implementation; thus, neither family nor deceased patient perspectives are included here.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las nubes de palabras se utilizan para la comunicación de palabras clave y ejemplos de su uso son el refuerzo a las familias de pacientes fallecidos que han sido tratados mediante un enfoque de medicina narrativa 14 ; como forma de resumir los artículos publicados en revistas científicas en función de los años 26 y para el análisis de datos clínicos cualitativos 27 .…”
Section: Discussionunclassified
“…Las nubes de palabras son colecciones de vocablos organizados en forma compacta, en donde el tamaño de la fuente codifica la relevancia de cada palabra en el documento 14,15 . Para la generación de las nubes de palabras se mapeó el valor de FT-FID de la palabra al tamaño de esta.…”
Section: Nubes De Palabrasunclassified